Challenges and Instructors’ Intention to Adopt and Use Open Educational Resources in Higher Education in Tanzania - Mtebe, Joel Samson; Raisamo, Roope (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
Higher education in Tanzania like in many other Sub-Saharan countries suffers from unavailability of quality teaching and learning resources due to lack of tradition, competence, and experience to develop such resources. Nevertheless, there are thousands of open educational resources (OER) freely available in the public domain that can potentially improve the quality of existing resources or help to develop new courses. The uptake and reuse of these resources in higher learning institutions (HLIs) in Tanzania has been very low. The study applied the unified theory of acceptance and use of technology (UTAUT) model to elicit instructors’ intention to adopt and use OER in teaching. The paper also investigated challenges that hinder instructors to adopt and use OER. A sample of 104 instructors selected randomly from five HLIs was collected and tested against the research model using regression analysis. The study found effort expectancy had significant positive effect on instructors’ intention to use OER while performance expectancy, facilitating conditions, and social influence did not have significant effect. Challenges that were found to hinder instructors to adopt and use OER are discussed. The findings of this study will help those who are involved in OER implementation to find strategies that will maximize OER adoption and usage in higher education in Tanzania.